Analisis Kesulitan Mahasiswa Sastra China dalam Menguasai Hanzi (Studi Kasus di Universitas Bina Nusantara, Darma Persada dan Kristen Indonesia) - Cendrawaty Tjong (Humaniora, 2012)
Hanzi is the written form of the Chinese language. It is one of ancient characters in the world and also is the most used letters now. Many university students think that hanzi is their main problem in learning Chinese language. In order to find the easiest way to master Chinese characters, the author conducted a study using   qualitative and quantitative methods by conducting surveys to universities, distributing questionnaires, doing a Chinese hanzi skill test, doing interviews with lecturers who teach hanzi course, and making an experiment according to the theory of hanzi expert in China. The results show that the difficulty of university students to master hanzi is divided to several parts, such as: the difficulty from the elements of hanzi, poor learning habits, the thought of students or lecturer who thought that hanzi is difficult, lack of motivation and lack of language environment. The results also show the the good methods to teach hanzi is not only focused on textbook or writing rules, but  also can teach knowledge or theories relating to, as well as providing, cultural knowledge contained in it.